2018
DOI: 10.12659/msm.907466
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Versus Non-Ischemic (Neurogenic) Myocardial Contractility Impairment in Acute Coronary Syndromes: Prevalence and Impact on Left Ventricular Systolic Function Recovery

Abstract: BackgroundNeurogenic mechanism is believed to contribute to left ventricular (LV) systolic dysfunction in acute coronary syndromes (ACS); its extreme form is known as takotsubo cardiomyopathy. However, the magnitude of neurogenic contribution to LV dysfunction in all-comer first-time ACS remains unknown.Material/MethodsIn 120 consecutive patients with first-time ACS (age 66.3±12.3years, 40 women) coronary angiograms were individually matched to the echocardiographic left ventricular (LV) segments (17-segment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Indeed, a randomized study showed that CR reduced fat weight without a reduction in lean body weight, and also reduced the levels of TC in older patients with CAD [41]. These direct and indirect effects may have led to the reduction in cardiovascular events, and these effects can predict MACE in ACS patients, such as neurogenic mechanism and CRP [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a randomized study showed that CR reduced fat weight without a reduction in lean body weight, and also reduced the levels of TC in older patients with CAD [41]. These direct and indirect effects may have led to the reduction in cardiovascular events, and these effects can predict MACE in ACS patients, such as neurogenic mechanism and CRP [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…According to the absence/presence of angiographically depicted lesions in a major epicardial vessel, CAGs were classified as showing the following: no CAD (normal coronary arteries, no luminal irregularity [ 26 ]) or CAD presence (‘any’ CAD) that was inclusive of stenosis(es) < 50% of the lumen diameter, stenosis(es) ≥ 50%, stenosis(es) ≥ 70%, occlusion(s) [ 3 8 ]. In addition, angiographic prevalence of the left main coronary artery (LM) stenosis ≥ 50% [ 3 ] was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…In general, coronary artery lesions with below 50% diameter stenosis (considered angiographically ‘insignificant’) require no interventional management but rather modification of risk factors and pharmacotherapy to prevent or minimize lesion progression and the risk of lesion destabilization [ 3 ]. On the other hand, patients with lesion(s) ≥ 50% (considered angiographically ‘significant’ CAD [ 4 8 ]) may benefit from procedural intervention (particularly in the case of documented myocardial ischemia [ 3 ]) and lesions ≥ 70% are usually considered to require intervention [ 3 ]. Thus unequivocal determination of CAD severity continues to play a fundamental role in clinical decision-making in contemporary cardiology.…”
Section: Introductionmentioning
confidence: 99%
“…NSC and TTS have been appropriately linked as having similar clinical presentation, histopathologic findings and most likely also pathophysiology, the only distinction being the presence or absence of structural or infectious brain insult [25,45]. The apical-sparing types of these conditions (basal, mid-ventricular and focal) remain largely undetected, due to their less vivid clinical presentation [4]. All these new data, delineating the very elusive and yet apparent brain-heart crosstalk, solidify the exciting emerging field of neurocardiology [4,25,[46][47][48][49].…”
Section: Stress Induces Acute Heart Failurementioning
confidence: 99%
“…On the other hand, intense acute emotional stress can cause severe medical conditions such as post-traumatic stress disorder (PTSD), takotsubo syndrome (TTS), deep venous thrombosis and pulmonary embolism (DVT/PE), and trigger myocardial infarction (MI), life-threatening arrhythmias and sudden cardiac death (SCD) [1][2][3]. Recent evidence indicates that the psycho-neurogenic component of the stress response is at least partially responsible for cardiac contractility impairment in one fourth of patients newly diagnosed with acute coronary syndrome (ACS) [4]. The effects of long-term psychological stress have been proven detrimental for human health.…”
Section: Introductionmentioning
confidence: 99%